Application of natural product-based quorum sensing inhibitors in plant pathogen control: A review - Ai-Qun Chen; Zhou-Qing Long; Ya Xiao; Yu-Mei Feng; Ya Zhou; Shan Yang; Yan-Mei Liao; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; Song Yang (Arabian Journal of Chemistry)
Quorum sensing (QS), an intercellular communication process, depends on the generation, release, and detection of extracellular signaling molecules (autoinducers). Upon binding to their corresponding receptors, these autoinducers activate target genes, regulating various bacterial activities including bioluminescence, swimming and swarming motility, symbiosis, protein secretion, plasmid exchange, secondary metabolite production, and biofilm development. Many interactions between plants and microorganisms depend on bacterial QS systems, making them a powerful tool for regulating plant growth and controlling plant pathogens. As QS research deepens, more QS inhibitors (QSIs) emerge, exhibiting diversification. According to its structure, QSIs can be divided into furanone, lactone, substituted Homoserine Lactone (HSL), and Autoinducing Peptide (AIP), further divided into natural products and synthetic products. Natural QSIs primarily originate from animal, plant, and microbial sources. Thereby, QSIs play an important role in plant pathogen control. In order to systematically summarize and extend the application potential of natural product as vital antibacterial active constituent, the mechanisms and applications of natural product-based QSIs in plant pathogen control were discussed and highlighted. We hope this review will provide the comprehensive understanding of the function and underlying action mechanism of natural product-based antimicrobial molecule, and inspire the development of new bactericides targeting QS mechanisms.